Analysis of The Need for Applied Science Teaching Materials in Chemical Materials in Vocational School, Department of Culinary, Tangerang District - Bella Nur Afinda; Sjaeful Anwar; Omay Sumarna (Global READ Center, 2023)
This study aims to explain the need for teaching materials in the culinary arts vocational school which will be developed using the 4S TMD method. This research is based on the problem of not integrating chemistry subjects in supporting vocational subjects with culinary skills competence. So there are no teaching materials that are relevant to the competence of culinary expertise. The data collection instrument used was the relevance format between chemical content and vocational content. This type of research is descriptive with a qualitative approach. The subjects in this study were two lecturers of chemistry education, two teachers of applied science, and three teachers of productive culinary arts who acted as validators. The results of this study became the basis for researchers in developing chemistry books using the 4S TMD method on applied science teaching materials for chemistry relevant to vocational skills in culinary skills.